Perspectives of Adolescent Girls and Young Women on Optimizing Youth-Friendly HIV and Sexual and Reproductive Health Care in Zambia - Patrick V. Edwards; Sarah T. Roberts; Nachela Chelwa; Lyson Phiri; Laura Nyblade; Drosin Mulenga; Caila Brander; Maurice Musheke; Michael Mbizvo; Sujha Subramanian (Frontiers Media S.A., 2021)
Youth-friendly health care delivery models are needed to address the complex health care needs of adolescent girls and young women (AGYW). The aim of this study is to explore the lived experiences of AGYW seeking comprehensive HIV and sexual and reproductive health (SRH) care and to elicit their preferences for integrated health care services. We conducted in-depth interviews and focus group discussions in Lusaka, Zambia among 69 AGYW aged 10-20 who were HIV-negative or of unknown status and 40 AGYW aged 16-24 living with HIV. The data were coded through deductive and inductive processes and analyzed thematically using modified World Health Organization (WHO) dimensions of quality for youth-friendly services. AGYW expressed preference for one-stop clinics with integrated services that could provide HIV services along with other services such as pregnancy testing and family planning. AGYW also wanted information on staying healthy and approaches to prevent disease which could be delivered in the community setting such as youth clubs. An integrated clinic should address important attributes to AGYW including short wait time, flexible opening hours, assurance of confidentiality and positive staff attitudes. Youth-friendly, integrated care delivery models that incorporate AGYW preferences may foster linkages to care and improve outcomes among vulnerable AGYW.